HUBUNGAN DISMENORHEA DENGAN AKTIVITAS REMAJA PUTRI DI SMPN 17 BURU TANJUNG KARANG KAB.BURU - Melawati Wakano; Indri Waimese (STIKES Pasapua Ambon, 2020)
Introduction: Dysmenorhea or menstrual pain is the characteristic pain that occurs before or during menstruation. Occurs on the first to several days for adolescents. In adolescents menstrual pain (dysmenorhea) is felt. Some often interfere with daily activities. This study aims to determine the relationship between dysmenorrhea and the activities of young women at SMPN 17 Buru Tanjung Karang. Method: The research design used is descriptive analytic, with a cross sectional approach to describe. The relationship between dysmenorrhea and the activities of young women at SMPN 17 Buru Tanjung Karang with a sample of 30 respondents. The research results obtained from 30 respondents at SMPN 17 Buru Tanjung Karang showed that the respondents who obtained most of the students who had good activities were 25 (83.3%) respondents. and those with poor activity were 5 (16.7%) respondents. While 21 students experienced dysmenorrhea, it was found that all of them (100%) experienced dysmenorrhea, whereas of the 9 students who did not experience dysmenorrhea (44.4%) did not experience dysmenorrhea. Result: The results of this study are recommended for respondents who experience menstrual pain (dysmenorhea) so that they can tolerate the pain that is felt by carrying out daily activities so that they do not experience interference. Conclusion: that menstrual pain is caused by several factors, including: Age, history of menstrual pain and social support from this family. They need to get treatment, such as taking analgesic drugs, warm compresses on the painful parts so they don’t interfere with their daily activities. teenage age.